Respuesta :
-1/8(2h + 4) + 1/2 = -7/4
-1/4h - 1/2 + 1/2 = -7/4
-1/4h = -7/4
h = -7/4 * - 4
h = 7 <==
-1/4h - 1/2 + 1/2 = -7/4
-1/4h = -7/4
h = -7/4 * - 4
h = 7 <==
Answer: A. 7
Step-by-step explanation:
The given equation : [tex]\dfrac{-1}{8}(2h+4)+\dfrac{1}{2}=\dfrac{-7}{4}[/tex]
Multiply 8 on both sides , we get
[tex]8\times\dfrac{-1}{8}(2h+4)+8\times\dfrac{1}{2}=8\times\dfrac{-7}{4}[/tex]
[tex]-(2h+4)+4=-14\\\\\Rightarrow\ -2h-4=-14-4\\\\\Rightarrow\ -2h=-18+4\\\\\Rightarrow\ -2h=-14\\\\\Rightarrow\ h=7[/tex]
Hence, the value of h= 7